(untitled) (Research, Society and Development, 2022)
Existing ethnobotanical and ethnopharmacological studies have as consensus that the Cerrado biome holds one of the greatest biological diversity of species, especially when it comes to plants with medicinal potential. Research on the medicinal flora of the Cerrado has been carried out for all states covered by the biome and considering the high degree of endemism that each region has in relation to certain species, these regions will present a medicinal flora with species common to others and with particular species. The methodology used in this study was the literature review and data analysis, which proved to be more appropriate for this type of research, because it aims to identify the quantitative and qualitative production of the theme in question in the last twenty years. In this study, a bibliographic survey of ethnobotanical and ethnopharmacological research ethnopharmacological scans addressing medicinal plants of the Cerrado was carried out. Based on the assumption that the Cerrado is a biome that presents an inestimable value due to its biodiversity, it is observed the need for research and appreciation of knowledge around the plant species present in this scenario. Another aspect that deserves to be highlighted is that the traditional herbal medicine is the one elaborated from a medicinal plant based on popular tradition, without known evidence of risk to the user’s health, whose efficacy is validated through ethnopharmacological and use surveys, scientific documentation, or indexed publications.